Formulation of an Anti-acne Cream Containing Ethanolic Extract of Purslane (Portulaca oleracea) - Isna Lailatusholihah; Dina Alva Prastiwi; Afiatun Ni'mah; Yudhistira Yudhistira (Biology, Medicine, & Natural Product Chemistry, 2025)
Portulaca oleracea (purslane) is a medicinal plant known for its antibacterial potential due to the presence of bioactive compounds such as saponins, tannins, flavonoids, and alkaloids. This study aimed to formulate an anti-acne cream containing the ethanol extract of P. oleracea and to evaluate its antibacterial activity against Staphylococcus aureus. The extract was obtained through maceration using 96% ethanol, and antibacterial testing was performed using the well diffusion method. The results showed that the ethanol extract demonstrated antibacterial activity, with the highest effect observed in formulation F3, which produced an inhibition zone of 13 mm (strong category). F3 also exhibited desirable physicochemical characteristics, including a spreading diameter of 6.5 cm, viscosity of 14,340 cP, and pH of 5, all of which complied with standard requirements. These findings indicate that P. oleracea ethanol extract has potential as an active ingredient in topical anti-acne formulations.